(untitled) (Texas Journal of Medical Science, 2026)
Sensorineural hearing loss significantly affects speech acquisition, cognitive development, and social adaptation in children. Investigation of the psycho-emotional profile of preschool children with sensorineural hearing loss is essential for developing effective interventions.